THE IMPACT OF CHRONIC HEART FAILURE ON HEALTH, EARLY DIAGNOSIS, AND PREVENTION (Western European Journal of Medicine and Medical Science, 2025)
Heart failure is a syndrome caused by decompensated myocardial dysfunction. It manifests itself as an increase in the volume of intercellular fluid and a decrease in perfusion of organs and tissues. The pathophysiological basis of this syndrome is that the heart cannot meet metabolic needs. It often develops as a complication of previous or current diseases that damage the heart muscle or put additional stress on it. In addition to the most common causes, there are other causes of heart failure. These include abnormal pressure in the blood vessels of the heart, diseases of the coronary arteries, heart valves and heart muscle, and arrhythmia. Sometimes heart failure is a complication of diseases of other organs, diseases that affect or damage the heart muscle. The most common cause of chronic heart failure is coronary artery disease. Heart failure can develop at any age, but is most common in older people